Female magnesium deficiency and its management: review of current knowledge - A. D. Makatsariya; V. O. Bitsadze; A. G. Solopova; O. A. Gromova; D. I. Korabelnikov; D. V. Blinov; J. Kh. Khizroeva; N. A. Makatsariya; M. V. Tretyakova; S. A. Akavova; D. M. Ampilogova (Акушерство, гинекология и репродукция, 2024)
Magnesium is an important cofactor for metabolic reactions involving more than 300 enzymes, regulating a series of fundamental processes, such as myocardial contraction and blood pressure control, glucose regulation, participation in neuromuscular transmission. The prevalence of magnesium deficiency in various cohorts of fertile age women comprises up to 73.8 %. In clinical studies it was demonstrated that magnesium deficiency is associated with diseases and states such as dysmenorrhea, premenstrual syndrome (PMS), polycystic ovary syndrome (POS), climacteric syndrome, osteoporosis, use of combined oral contraceptives (COCs) and menopausal hormone therapy (MHT). Magnesium supplementation in combination with basic therapy can positively affect course and outcome of such pathologies. Magnesium organic salts could be used for countering magnesium deficiency. Among such agents, magnesium citrate has some advantage used in combination with pyridoxine (vitamin B6) providing additional effects. Health care professionals should be guided by the criteria for Mg-containing preparation selection, defined by the Russian Society of Obstetricians and Gynecologists (RSOG).